My master's robe : memories of a novice monk - Nhất Hạnh, Thích (Parallax Press, 2002)
A collection of autobiographical stories highlighting Thich Nhat Hanh's experience as a novice monk in Vietnam. We are given a portrait of Thich Nhat Hanh as a young man testing the Buddhist teachings, planting seeds that would carry him through the ordeals of the Vietnam War and its aftermath.